Trajetórias e processos inovativos: um olhar evolucionário em casos da pecuária familiar na Campanha Gaúcha - Langbecker, Tatielle Belem (2020)
This thesis aims to analyze a historical trajectory of family farming in the Gaúcha Campaign and the influence of innovative processes in the adaptation and maintenance of productive activities in a changing scenario. As a theoretical perspective, the research is based on evolutionary economics, especially on theoretical constructs that define innovative processes and their constituent elements such as, for example, learning, knowledge, path dependence, trajectories, changes, among other things. The construction carried out in the theoretical review was the base for the construction of the framework and, consequently, the research instrument that identifies the trajectories of the firms since their historical-family origin, insertion in the activity, general changes in the scenario and, finally, the changes that occurred in the routines of the firms. The constructs used allow the analysis of routines showing the links between past, present and constant changes in dynamic agricultural scenarios. For that, we used the case study supported by a qualitative approach. Three cases of family ranching in the Gaúcha Campaign were analyzed: Association of Producers of Rincão do 28 (Alegrete), participants of RS Biodiversidade (Alegrete) and family ranchers who perform sheep crossings (Santana do Livramento). From the analysis of thematic-categorical content, it was possible to identify that all units investigated have a family history in the activity, albeit in different forms. Most interviewees' insertion in innovative processes is associated with stimuli and policies external to the units; the participation in technical courses, the contact with the public rural extension service and the proximity to other non-profit organizations, associated with the experiences, determines the format adopted in each family unit. This contact with institutions, courses and experiences results in the adaptations that family farmers make in the techniques and technologies presented to them. This dynamics found in family ranching corroborates the logic of an innovative process of evolutionary economics, in which innovation is conditioned by the firms’ learning formats, by the previous experiences and the trajectories’ history that the routines followed along the activity. Thus, adaptations in the routines of family farming activities are driven by innovative processes. The relationship between historical trajectory and learning in the activity defines the adaptations made in each unit of family livestock, therefore, identifying such adaptations as endogenous innovations. In the case of Associação do 28, it was observed the potential that collective proposals have in bringing family farming to the “current” technologies, as well as transforming the perception of the activity in the face of changing scenarios. In addition, two specific situations were identified to be assessed as particular cases of entrepreneurship. Finally, it is considered that understanding the innovative processes in family farming combined with rescue as a productive alternative, contributes to pointing out adaptations to production systems, not in the sense of "transforming" the activity, but to stimulate variations in family farming generated by changes in routines and, with that, favor the consolidation of an alternative agricultural technological paradigm that maintains the historical family cattle farming in its original environment.